PENERAPAN MEDIA STANDING BOARD UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Aryo Bhimo Yusup; Din Azwar Uswatun (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
Science education in elementary schools often faces challenges in creating an engaging and meaningful learning environment. One of the main obstacles is the use of lecture-based methods, which make students less active and result in low learning outcomes. This study aims to evaluate the use of standing boards as an alternative visual learning medium in improving student learning outcomes on the subject of animal classification based on habitat and reproduction methods. The study was conducted using the Classroom Action Research (CAR) method, consisting of two cycles in Grade VI of SD Negeri Lembursitu, Sukabumi City. The instruments used included achievement tests and observation sheets for student and teacher activities. The results showed an increase in the average student score from 68 in the pre-cycle to 76 in cycle I, and reached 85 in cycle II. Student learning activities also showed positive development in engagement and participation during the learning process. In conclusion, the use of standing boards proved effective in improving students' science learning outcomes and fostering a more interactive and enjoyable learning process.